2018
DOI: 10.3390/nu10121998
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin, a Flavonoid-Based Compound of Leopard Lily Rhizome, Attenuates UV-B-Induced Apoptosis and Collagen Degradation by Inhibiting Oxidative Stress in Human Keratinocytes

Abstract: Ultraviolet (UV) light, a major risk factor for external skin photoaging, induces oxidative stress in skin. UV causes a breakdown of skin homeostasis by impairing the extracellular matrix and inducing cell death. Tectorigenin, a constituent of leopard lily (Belamcanda chinensis L.) rhizome, has been reported to possess antioxidant, hair-darkening, and anti-inflammatory activities; however, the effect of tectorigenin on UV-B-induced skin damage is unknown. Here, we investigated the anti-skin-damage effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The UV irradiation enhances ROS production and activates proinflammatory pathways, including biosynthesis of prostaglandins and “the death ligands”, especially TNFα, which activates the extrinsic pathway of apoptosis through caspase 8 [ 55 ]. Other authors also point to the role of caspases 3 and 8 in the apoptosis of keratinocytes from healthy people after exposure to UVB irradiation [ 56 , 57 ], but so far there have been no data on the response of psoriatic keratinocytes. The results of our study indicate that UVB leads mainly to the activation of the extrinsic apoptotic pathway in healthy and psoriatic cells, likely due to its impact on the level of proapoptotic 15-d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The UV irradiation enhances ROS production and activates proinflammatory pathways, including biosynthesis of prostaglandins and “the death ligands”, especially TNFα, which activates the extrinsic pathway of apoptosis through caspase 8 [ 55 ]. Other authors also point to the role of caspases 3 and 8 in the apoptosis of keratinocytes from healthy people after exposure to UVB irradiation [ 56 , 57 ], but so far there have been no data on the response of psoriatic keratinocytes. The results of our study indicate that UVB leads mainly to the activation of the extrinsic apoptotic pathway in healthy and psoriatic cells, likely due to its impact on the level of proapoptotic 15-d-PGJ 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Bax activates caspase‐3 and induces the release of cytochrome c in mitochondria. The activated caspase‐3 is Cleaved Caspase‐3 (Noh et al, 2018). Studies have shown that Tectorigenin inhibits apoptosis by suppressing caspase‐3 and Bax levels and promoting Bcl‐2 protein level (Noh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The activated caspase‐3 is Cleaved Caspase‐3 (Noh et al, 2018). Studies have shown that Tectorigenin inhibits apoptosis by suppressing caspase‐3 and Bax levels and promoting Bcl‐2 protein level (Noh et al, 2018). Our results showed that Dex promoted the expressions of Bax and Cleaved Caspase‐3, but inhibited the expression of Bcl‐2, which was further reversed by Tectroigenin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations